Surgical Patient Compliance With Healthcare Facility–Provided In-home Opioid Disposal Products: A Systematic Review. (January 2022) - Edwards, John M.; Evans, Hallie; Dollar, Stace D.; Odom-Forren, Jan; Johnson, Bill
Abstract : OBJECTIVE: The aim of this study was to review the literature regarding the use of an in-home opioid disposal product on unused opioids after surgery. BACKGROUND: The opioid epidemic in the United States is a major cause of concern for healthcare facilities. The misuse and diversion of retained opioids after a surgical procedure continues to contribute to this problem. METHODS: A comprehensive search of the Cumulative Index of Nursing and Allied Health Literature, OVID, and PubMed databases with keywords including opioid, analgesics, narcotics, medical waste disposal, medical disposal, refuse disposal, and opioid disposal resulted in 286 articles. Articles were screened based on strict inclusion and exclusion criteria. RESULTS: Eight studies determined that an in-home opioid disposal product provided by a healthcare facility produced rates of opioid disposal between 19% and 71%. CONCLUSIONS: The provision of an in-home opioid disposal product by a healthcare facility is likely to increase the disposal of unused opioid medications in the postoperative surgical patient population. Abstract : Supplemental digital content is available in the text.